2019
DOI: 10.1111/his.13797
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 5B, carbonic anhydrase 9 and claudin 18 are potential theranostic markers of gallbladder carcinoma

Abstract: Aims Gallbladder cancer (GBC) is an aggressive tumour that is usually diagnosed at advanced stages and is characterised by a poor prognosis. Using public data of normal human tissues, we found that mRNA and protein levels of mucin 5B (MUC5B) and carbonic anhydrase 9 (CA9) were highly increased in gallbladder tissues. In addition, previous evidence has shown that claudin 18 (CLDN18) protein expression is higher in GBC. The aim of this study was to perform an analysis of these cell surface proteins during the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Interestingly, PI3K actively participates in the regulation of the immune response [77], suggesting that early alterations in PI3K could drastically alter the balance of the inflammatory response. Furthermore, Espinoza et al also described Claudin-18 (CLDN-18) as a membrane marker of gallbladder metaplasia within the progression sequence towards GBC, where the CLDN-18 expression is also present in ~50% of gallbladder tumors [78].…”
Section: Inflammation In Gallbladder Carcinogenesismentioning
confidence: 99%
“…Interestingly, PI3K actively participates in the regulation of the immune response [77], suggesting that early alterations in PI3K could drastically alter the balance of the inflammatory response. Furthermore, Espinoza et al also described Claudin-18 (CLDN-18) as a membrane marker of gallbladder metaplasia within the progression sequence towards GBC, where the CLDN-18 expression is also present in ~50% of gallbladder tumors [78].…”
Section: Inflammation In Gallbladder Carcinogenesismentioning
confidence: 99%
“…Two out of the five biomarkers (CLDN18 and CA9) highlighted in this review have also been reported as potential theranostic targets in gallbladder cancer [ 105 ]. EGFR and MMP9 have long been areas of research focus in cancer theranostics.…”
Section: Discussionmentioning
confidence: 99%
“…The score can range from 0 to 300. In this study, a cutoff of 50 was used, and scores were categorized as negative or low (0–50) and positive or high (51–300) 19,20 . The criterion for subclonal CLDN18 was defined as abnormal staining of more than 12 consecutive cells on the background of abnormal CLDN18 staining 21 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a cutoff of 50 was used, and scores were categorized as negative or low (0–50) and positive or high (51–300). 19 , 20 The criterion for subclonal CLDN18 was defined as abnormal staining of more than 12 consecutive cells on the background of abnormal CLDN18 staining. 21 P16 was evaluated as positive with diffuse, block‐like expression, whereas no or patchy expression was negative.…”
Section: Methodsmentioning
confidence: 99%